Cohabitability of human reality in post-pandemic times (Revista Electrónica REDINE, 2023)
The classification of a pandemic by the World Health Organization (WHO) with respect to Covid-19 constitutes a universal contingency of singular importance, it has called for the need to examine the foundations on which humanity has been built and in particular, on this side of the world, Western culture, leading to a critical review that invokes many questions, including the philosophical order. This article, assumed from the documentary method forged by consulting various theorists, including Morin (1999), Kosik (1965) and Sorokin (1970), reflects on the ontological perspectives of reality, captured from the empiricist or rational perception, but without dismissing the spiritual, suprarational and intuitive vision. In this way, one reflects on the world as reality and axiological considerations are made regarding the ontological dilemma that undoubtedly lead to evaluative deliberations of an ethical nature. Likewise, the condition of love is explored as ferment and driving force that encourages any possibility of change, arising in consideration of the recognition of the other and respect for biodiversity. Finally, it is concluded about the importance of producing a turn of the helm that allows to modify the patterns of thought, proposing the approach of issues such as exclusion, self-determination, human rights, visibility of minorities, and recomposition of relations between peoples, through criteria that respect diversity.
Keywords: Covid-19 pandemic; cohabitable reality; ontological perspective; axiological considerations